EFFECTIVENESS OF THE STATUTORY ROLE OF FEDERAL ROAD SAFETY CORPS IN REDUCTION OF ROAD TRAFFIC CRASHES IN KOGI STATE, NIGERIA - Dangana- Onuche, Gloria Ojonoka; Damsa, Torungwa Justin (African Journal of Social and Behavioural Sciences, 2024)
Road traffic crash is one of the major causes of death for young people worldwide. Mortality and injury related to fatal accident are increasing partly due to the level of motorization. This paper therefore examines the effectiveness of the statutory role of the Federal Road Safety Corps (FRSC) in the reduction of road traffic crashes in Kogi State, Nigeria. Data for the study was elicited from 400 respondents across the three senatorial districts in the study area using semi-structured questionnaires and analysed quantitatively using descriptive statistics. Findings from the study revealed that; out of the 20 statutory roles of the FRSC in Kogi State, only six were discharged effectively which denotes that their operational is not satisfactory. The study also found that behavioural problems on the parts of motorists and other road users, poor road design, improperly placed or absence of road signs and lack of maintenance of existing roads, untimely implementations, evaluation of road safety programmes and inadequate founding of the commission were the contributory factors to the ineffectiveness of the statutory roles of the FRSC (54.7%). The study therefore recommends among others that, a consistent and collective effort from the government, stakeholders and behavioural change on the part of the individuals can help to achieve sustainable road safety practices in Nigeria. More importantly, the FRSC should be stricter in enforcing road safety precautions in terms of the use of seat belt, use of mobile phones while driving, speed limits, the use of speed limit devices and giving of prompt medical attention and care to accident victims on the road.